A thermoresponsive nanocarrier for mitochondria-targeted drug delivery. Issue 28 (14th March 2019) - Wang, Dongqing; Huang, Hui; Zhou, Mengxue; Lu, Huiru; Chen, Jun; Chang, Young-Tae; Gao, Jimin; Chai, Zhifang; Hu, Yi
Abstract : A thermoresponsive nanocarrier was developed for mitochondria-targeted drug delivery. Abstract : Mitochondria emerge as an important target for cancer therapy. Herein, by taking advantage of the recently reported high temperature of mitochondria, a well-tuned thermoresponsive nanocarrier was developed for specifically delivering the anticancer drug, paclitaxel (PTX), to mitochondria in cancer cells. The temperature-dependent delivery of drugs to mitochondria represents a novel anticancer strategy.